Before and after analysis of the bridge to Askøy - Tørset, Trude (Proceedings from the Annual Transport Conference at Aalborg University, 2006)
Askøy is an island near the city centre of Bergen, consisting of about 20 000 residents. Bergen is the second largest city of Norway consisting of about 250 000 inhabitants including the commuting area. Until the bridge “Askøybroen” was opened in December 1992, the only transport option between Askøy and Bergen was a ferry. Three travel surveys are used in this study, the first was carried out just before and the second just after the opening of the bridge. The third was carried out a few years later, giving the travel habits time to settle. The three travel surveys give us a rare opportunity to check out how the bridge influenced the travel patterns in real life, compared to how the changes were calculated in a typical four-step transport model. This paper describes problems in the transport model regarding several issues, among them how ferries are described and the relation between car-availability and car-density used in the model.